1985
DOI: 10.1002/jcc.540060111
|View full text |Cite
|
Sign up to set email alerts
|

Ab initioSCF MO calculations on the reactions of hydroxyl radical with imidazole and monoprotonated imidazole

Abstract: The addition reactions of hydroxyl radical with imidazole and its protonated form to yield radical adducts have been investigated by ab initio SCF MO methods using s~o -3 G and 4-31G basis sets. Analogous radical species are of importance in radiation damage to biological systems. Of the possible radical products, the calculations indicate that the allylic species are generally favored energetically over the nonallylic forms. On an energetic basis, the results show that the allylic adducts formed by addition a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1

Year Published

1986
1986
1986
1986

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 23 publications
0
6
1
Order By: Relevance
“…Although more information exists regarding reactions of OH with thymine and uracil, the greater experimental controversy for site preference of OH addition to cytosine lent impetus to the choice of cytosine as a subject for these calculations. A recent paper (8) suggested that site selection of OH attack of cytosine is more discriminating than for the analogous reactions with thymine and uracil and that the major product, in opposition to expectations from the results of our previous studies on OH reactions with N heterocycles (1,2), was the species favored on account of electrophilic interactions rather than being the most electronically delocalized product. These factors contributed to the selection of cytosine as the subject for study.…”
Section: Introductioncontrasting
confidence: 61%
See 4 more Smart Citations
“…Although more information exists regarding reactions of OH with thymine and uracil, the greater experimental controversy for site preference of OH addition to cytosine lent impetus to the choice of cytosine as a subject for these calculations. A recent paper (8) suggested that site selection of OH attack of cytosine is more discriminating than for the analogous reactions with thymine and uracil and that the major product, in opposition to expectations from the results of our previous studies on OH reactions with N heterocycles (1,2), was the species favored on account of electrophilic interactions rather than being the most electronically delocalized product. These factors contributed to the selection of cytosine as the subject for study.…”
Section: Introductioncontrasting
confidence: 61%
“…The more extensively electron delocalized C6 adduct is calculated to be more stable relative to the C4 adduct and the experimentally found C5 adduct. In earlier theoretical studies (2,22,(26)(27)(28), an arbitrary value of 40 kJ/mol was set as the limit of significant energy difference; thus, the small energy difference between the C4 and C5 adducts (5 kJ/mol) suggests similar stabilities, and no conclusive ordering in their relative stabilities can be made.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations